The world's second record of Neoheteroceras flageoletii reported from Turkey - Huseyin, Elsad; Selcuk, Faruk; Sahin, Ahmet (Mycotaxon Ltd, 2005)
Neoheteroceras flageoletii, a rare coelomycete, with appendage-bearing conidia, is reported and illustrated from Turkey on Tilia rubra subsp. caucasica. It is a second locality of this fungus.
Keywords: anamorphic fungi; morphology